Natural convection in a wavy porous cavity with sinusoidal heating and internal heat generation - Cheong, Huey Tyng; Sivasankaran, Sivanandam; Bhuvaneswari, Marimuthu (Emerald, 2017)
Purpose - The purpose of this paper is to study natural convective flow and heat transfer in a sinusoidally heated wavy porous cavity in the presence of internal heat generation or absorption. Design/methodology/approach - Sinusoidal heating is applied on the vertical left wall of the cavity, whereas the wavy right wall is cooled at a constant temperature. The top and bottom walls are taken to be adiabatic. The Darcy model is adopted for fluid flow through the porous medium in the cavity. The governing equations and boundary conditions are solved using the finite difference method over a range of amplitudes and number of undulations of the wavy wall, Darcy-Rayleigh numbers and internal heat generation/absorption parameters. Findings - The results are presented in the form of streamlines, isotherms and Nusselt numbers for different values of right wall waviness, Darcy-Rayleigh number and internal heat generation parameter. The flow field and temperature distribution in the cavity are affected by the waviness of the right wall. The wavy nature of the cavity also enhances the heat transfer into the system. The heat transfer rate in the cavity decreases with an increase in the internal heat generation/absorption parameter. Research limitations/implications - The present investigation is conducted for steady, two-dimensional natural convective flow in a wavy cavity filled with Darcy porous medium. The waviness of the right wall is described by the amplitude and number of undulations with a well-defined mathematical function. An extension of the present study with the effects of cavity inclination and aspect ratio will be the interest for future work. Practical implications - The study might be useful for the design of solar collectors, room ventilation systems and electronic cooling systems. Originality/value - This work examines the effects of sinusoidal heating on convective heat transfer in a wavy porous cavity in the presence of internal heat generation or absorption. The study might be useful for the design of solar collectors, room ventilation systems and electronic cooling systems.